Analysis of Student’s Creative Thinking Ability in Mathematical Problem Solving in Terms of Extrovert and Introvert Personality Types - Habibah Intan Sari; Mumun Munawaroh; Hendri Raharjo (EduMa: Mathematics education learning and teaching, 2020)
Analysis of Student’s Creative Thinking Ability in Mathematical Problem Solving in Terms of Extrovert and Introvert Personality Types. This research is motivated by differences in personality types that cause differences in creative thinking ability based on its level. Therefore, indicators of creative thinking ability used are fluency, flexibility, and originality. The research method used is descriptive with a qualitative approach. The research subjects were 4 students of class X IPS MA An-Nur Cirebon City which were selected based on consideration of the results of personality tests. The instruments used were personality tests, tests of creative thinking ability, and interviews. Data analysis techniques include data reduction, triangulation, data presentation, and concluding. The results showed that: (1) Students who tended extrovert personality types were at the level of creative thinking ability 1 (less creative). (2) Students who tended introvert personality types were at the level of creative thinking ability 3 (creative)